Tikuna Perceptions of Extreme Weather Events: A Case Study on an Indigenous Lands in the Upper Solimões River, Brazil - Lago, Maiana Costa do; Rebelo, George Henrique; Bruno, Ana Carla; Henriques, Luiza Magalli Pinto (Ethnobiology and Conservation, 2024)
The synergistic effects of extreme weather events and socioecological vulnerability are still poorly documented for Amazonian indigenous peoples. Herein, we investigated the impacts of recent extreme weather events on Tikuna villages. Tikuna are ancient people of the Amazon, with an estimated population of approximately 53 thousand people widely distributed along the upper Solimões River in the western Brazilian Amazon. The fieldwork was carried out between October 10 and December 10, 2018, using participatory research, including focus group interviews and free-listing exercises. Four extreme weather events were recalled, namely, the extreme floods of 2009, the subsequent extreme drought of 2010, and the extreme floods of 2012 and 2015. The results indicated that Tikuna from some villages are adopting migration from floodplain habitats to nonflooded lands as a coping strategy to increase the frequency and intensity of extreme weather events. This process was characterized by famine periods, internal divisions, and increased vulnerability. The three villages have rich traditional knowledge and live on a large diversity of biological resources, base for a fishing economy and for an agroforestry system, the original indigenous subsistence agriculture with a high level of self-sufficiency in terms of food. Until our study, Tikunas had not received any information about the global climate emergency. Our findings can contribute to formulating public policies to provide support for adapting to climate change. These policies must ensure the participation of the Tikuna and other indigenous peoples in local and national discussions on climate change, strengthening their capacity to develop adaptation strategies based on their ancestral knowledge.